Management of soft tissue knee injuries in an accident and emergency department: the effect of the introduction of a physiotherapy practitioner. Issue 1 (1st January 2003) - Jibuike, O O; Paul-Taylor, G; Maulvi, S; Richmond, P; Fairclough, J
Abstract : Objective: To assess the effect of the introduction of a physiotherapist with an extended scope of practice in the management of acute soft tissue knee injuries in an accident and emergency (A&E) department. Methods: The A&E department established an Acute Knee Screening Service (AKSS) in 1998. An experienced physiotherapist was appointed to run the AKSS after additional training. Local guidelines and protocols were developed in conjunction with trauma knee surgeons, radiologists, physiotherapists, and A&E doctors. This study describes 100 consecutive patients managed by the AKSS over a three month period and comparisons are made over a similar period before the introduction of the AKSS. Results: The initial diagnosis of patients with acute knee injuries referred to the service showed meniscal injuries (38%), cruciate ligament injuries (18%), fractures (2%), patellofemoral joint injuries (10%), and others (32%). Ninety five per cent of patients referred to AKSS were seen within one week. Medical time was saved in both A&E and trauma clinic. Fifty nine per cent of patients were treated and discharged from the service without further medical review. Thirty nine per cent (39) were referred to trauma clinic and of these 44% (17) had MRI scans performed as requested by the physiotherapist. Eighty eight per cent (15) of these scans showed significant abnormality: (nine, anterior cruciate ligament tears, one, posterior cruciate ligament tears, and nine meniscal tears). Conclusions: A physiotherapy practitioner working with an extended role is a valuable addition to an A&E department. The AKSS improves the quality of care of acute knee injuries, saves medical time, and fosters cooperation across services within the NHS.